Hard template-induced internal solidification synthesis of Cu NPs- supported glutaraldehyde-crosslinked polyethyleneimine-modified calcium alginate beads with enhanced catalytic activity - Wang, Shifu; Xiao, Zuoyi; Ma, Xiuping; Zhao, Zhenyu; Guo, Dongmei; Chen, Yu; Zhai, Shangru; An, Qingda; Yang, Dongjiang (Applied catalysis. A, General, 2018)
A hard template-induced internal solidification strategy was developed to prepare a hydrogel bead-supported catalyst with ultrafine Cu NPs, high specific surface area and well-developed hierarchical pore structure, which exhibited remarkably catalytic activity and high stability. [Display omitted] •CaCO3 NPs were not only employed as a traditional hard template, but also as an indirect curing agent for calcium alginate beads.•The successful introduction of PEI could effectively dominate the distribution and the morphology of Cu NPs.•Cu@GLA-PEI-CA-1 beads exhibited enhanced catalytic activity and high stability for the reduction of 4-NP in aqueous solution.•Cu@GLA-PEI-CA-1 beads have the advantages of low cost, environmental protection, durable activity and easy recovery in the catalytic reaction. The development of a sustainable catalyst with high catalytic activity and easy recovery property is an important subject in the field of heterogeneous catalysis. In this work, we developed a hard template-induced internal solidification procedure for preparation of ultrafine metal nanoparticles (NPs) supported on GLA-PEI-CA beads. During the fabrication process, CaCO3 NPs had a dual function, not only serviced as a hard template to adjust the structure of the as-prepared catalyst, but also as an indirect crosslinking agent to obtain hydrogel beads. The resulting beads were characterized using FT-IR, XRD, BET, SEM, TEM, EDS and XPS. The results revealed that Cu NPs with a narrow size distribution in 2–3 nm were uniformly immobilized on the surface of GLA-PEI-CA-1 beads with high specific surface area and well-developed hierarchical pore structure. As a result, the Cu@GLA-PEI-CA-1 beads exhibited remarkably catalytic activity and high stability, with more than 90% conversion within 10 successive cycles, towards the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) by NaBH4 in aqueous solution. The result showed that the Cu@GLA-PEI-CA-1 catalyst displayed high kinetic responses with a kinetic reaction rate constant of 1.60 × 10−2 s−1, which was higher than that of Cu@GLA-PEI-CA-0 (without CaCO3 template) and Cu@GLA-CA-1 (without PEI coating). The enhanced catalytic performance was resulted from homogeneous distribution of Cu NPs along with the tailored microstructure and the hydrophilic surface of the support. Additionally, the dynamic catalytic experiment was conducted to investigate the catalytic performance of Cu@GLA-PEI-CA-1 beads as the catalyst. We expected that this work could provide a new and effective strategy to design highly efficient catalysts for various catalytic reactions.